Analysis of Metacognitive Ability of Middle School Students in Science Learning by Using Reflection Blogs - Astutik, Kartika Fitri; Wusqo, Indah Urwatin (Universitas Negeri Semarang, 2023)
This study aims to analyze the metacognitive abilities of junior high school students through reflection blogs. This study uses the type of research One-Shot Case Study. The sampling technique in this study used a purposive sampling technique. Based on the questionnaire data, metacognitive ability was obtained with an average score of 155.5 or 78.94% in class VIII A and metacognitive ability with an average score of 153.15 or 55%. Similar to the results of the questionnaire, the data for writing reflection blogs on students showed a score of 66% in class VIII A and 63% in class VIII B. Based on these data, it was found that the metacognitive abilities of class VIII A and class VIII B students were in the high category.